Adaptation of the quiet quitting scale for teachers to Turkish culture: An empirical psychometric investigation - Alanoglu, Muslim; Karabatak, Songul; Uslukaya, Alper; Kuloglu, Aysenur (Izzet Kara, 2024)
The study aims to introduce to the Turkish culture a measurement tool that has proven validity and reliability in determining the level of quiet quitting among teachers. It involves the analysis of the validity and reliability of the Quiet Quitting Scale, as the scale is adapted to the Turkish culture. The scale, originally developed in English, was adapted to Turkish using data from teachers employed in public schools who were selected through convenience sampling. Confirmatory factor analysis was initially used to assess the construct validity of the original structure of the scale within the Turkish context. The findings indicated a good fit to the four-factor model, supported by adequate factor loadings and fit indices, thus confirming the scale's validity within the Turkish culture. Reliability evaluation included internal consistency coefficients, test-retest stability, and composite reliability, all exceeding the threshold values. The test-retest analysis confirmed the stability of the scale, while the composite reliability analysis further supported its reliability. Measurement invariance across gender and tenure was examined, confirming that the scale can provide reliable comparisons across these demographic groups. Overall, these results demonstrate the successful adaptation of the Quiet Quitting Scale to Turkish culture and are supported by strong evidence of its validity and reliability.
Keywords: Quiet quitting; Teacher; Scale adaptation.